ACUTE PAIN NURSING CARE WITH CONGESTIVE HEART FAILURE - Fitria, Fatkhiyatul; Ilkafah, Ilkafah; Prasetyo, Cucuk Rachmadi (Universitas Airlangga, 2020)
Introduction: Patients with congestive heart failure usually have problems nursing chest pain. To reduce pain problems, there are several therapies that can be done, namely deep breath relaxation techniques, guide imagery techniques, and environmental management. The preferred therapy in this case is nonfaramcological, which is a deep breath relaxation technique. The purpose of this study was to provide acute pain nursing care for Congestive Heart Failure patients in the Heart Room at Dr. Soegiri Lamongan Hospital. Methods: Case study used to explore this study. Data collection is obtained through: interviews, observation, physical examination and documentation study. Analyzed case study results. From the discussion between literature review and case review, it is concluded that there is suitability from diagnosis to evaluation. Results: the case studies show an agreement between theoretical review and case review in patients. Evaluation of the Acute Pain nursing diagnoses, the problem was resolved on the third day. Conclusion: from the research conducted, found that deep breath relaxation technique is one of the effective non-pharmacological pain management methods to reduce pain.